Potensi Lengkuas Sebagai Bahan Pengawet Ikan: Review - Siti Aminah; Yunan Kholifatuddin Syadi; Muhammad Yusuf; Sri Hartati (Jurnal Pangan dan Gizi, 2023)
Galangal (Alpinia galanga) is a type of spice that is widely used as a spice and medicine. Galangal bioactive components such as flavonoids, terpenoids and phenolics have the potential to be antibacterial. Today has been widely studied the potential of galangal as an alternative preservative for natural food and fresh fish has characteristics that are prone to damage, especially microbiological damage, this is influenced by the characteristics of fresh fish with high water content, neutral pH and soft texture, microorganisms that destroy fresh fish include: Bacillus alvei, Pesudomonas aerogenosa, and Staphylococcus saprophyticus. Flavonoids, terpenoids and phenolics and other bioactiv components in galangal are able to inhibit bacterial growth in fish through mechanisms such as damaging bacterial cell walls, disrupting cell osmosis pressure and cell wall formation. Literature search both from research journal, theses and books. This review will be discussed the ability of galangal to inhibit microorganisms that destroy fresh fish and future research opportunities for formulations of natural ingredients as preservatives. Galangal has the potential as a preservative for fish trough the mechanism of inhibiting the growth of destructive microorganisms.